Exploring associations between skin, the dermal microbiome, and ultraviolet radiation: advancing possibilities for next-generation sunscreens - Smith, Matthew L.; O’Neill, Catherine A.; Dickinson, Mark R.; Chavan, Bhaven; McBain, Andrew J. (Frontiers in Microbiomes, 2023)
Recent studies have provided strong evidence of a functional link between the microbiota of the skin and overall host health. While sunscreens offer protection against acute and chronic dermatological damage by reflecting, absorbing and scattering ultraviolet radiation, their impact on the skin microbiota is poorly understood. The use of sunscreens may affect the skin microbiota directly or indirectly through mechanisms associated with UV protection, and conversely, the microbiota could mediate or alleviate UV-induced skin damage. Here we consider opportunities for the development of improved sunscreens including formulas that work in tandem with skin commensal microorganisms or which minimise direct effects on the skin microbiota.